2002
DOI: 10.1007/s00424-002-0866-1
|View full text |Cite
|
Sign up to set email alerts
|

Glucose dependence of insulinotropic actions of pituitary adenylate cyclase-activating polypeptide in insulin-secreting INS-1 cells

Abstract: The cAMP-elevating pituitary adenylate cyclase-activating polypeptide (PACAP) stimulates insulin release in pancreatic B-cells. Here, we have investigated its potentiating action in rat insulinoma INS-1 cells. In intact cells, PACAP-27 (100 nM) stimulated glucose-induced insulin secretion by >60%. Using the patch-clamp technique with single-cell exocytosis monitored as increases in cell capacitance, we observed that at 10 mM and 20 mM extracellular glucose, PACAP-27 acted mainly by a >50% enhancement of depola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
(55 reference statements)
1
4
1
Order By: Relevance
“…Indeed, experiments performed on INS-1 cells has previously demonstrated that a depolarization of the same size and duration (300 ms) can give rise to large differences in Ca 2+ influx measured as charge ( Q ). Plotting ΔC m to Q in this case gave a linear relationship [35]. Our data showed a near-linear ΔC m to Q relation (Fig.…”
Section: Resultssupporting
confidence: 68%
“…Indeed, experiments performed on INS-1 cells has previously demonstrated that a depolarization of the same size and duration (300 ms) can give rise to large differences in Ca 2+ influx measured as charge ( Q ). Plotting ΔC m to Q in this case gave a linear relationship [35]. Our data showed a near-linear ΔC m to Q relation (Fig.…”
Section: Resultssupporting
confidence: 68%
“…Similarly, Wan et al (2004) report a complete block of the forskolin-induced enhancement of HCSP and RRP pool sizes by Rp-cAMP. These findings are surprising because previous reports describe only a partial block of the cAMP-induced enhancement of depolarization-evoked exocytosis by PKA inhibitors in mouse β cells and INS-1 cells ( Renstrom et al, 1997 ; Rosengren et al, 2002 ). This has led to the hypothesis that cAMP enhances exocytosis through a PKA-independent pathway such as cAMP-GEFII ( Eliasson et al, 2003 ).…”
Section: Discussioncontrasting
confidence: 65%
“…Glucose triggers insulin release from pancreatic β cells by closing ATP/ADP-gated K + channels, which leads to membrane depolarization, Ca 2+ influx through voltage-gated Ca 2+ channels, and [Ca 2+ ] i -triggered exocytosis of insulin-containing granules. Glucose also promotes exocytosis from β cells independently from effects on K + (ATP) channels ( Eliasson et al, 1997 ; Takahashi et al, 1999 ; Rosengren et al, 2002 ). For example, elevated ATP levels may increase the number of vesicles in a readily releasable state.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations